Parental Violence and Family Stressors: A Comparative Study of Czech Adolescents in 2013 and 2023 - Podaná, Zuzana (Journal of contemporary criminal justice, 2025)
This study investigates the use of corporal punishment among Czech parents in the years 2013 and 2023, drawing on data from the third and fourth waves of the International Self-Report Delinquency Study (ISRD3 and ISRD4). The Czech Republic provides a unique case, having recorded the highest levels of parental violence—both minor and severe—among European countries participating in ISRD3. The article examines changes in the prevalence and incidence of parental violence over the past decade and explores its association with adverse family environments, including parental conflict, substance abuse, and economic disadvantage. Findings reveal a significant decline in the prevalence of minor corporal punishment, suggesting a gradual cultural shift away from its normative acceptance. However, the intensity of parental violence and the prevalence of its severe forms have remained stable. While risk factors related to adverse family environments are associated with severe parental violence in both ISRD waves, their impact on minor violence is weaker and has become more pronounced in disadvantaged neighborhoods over time. The results suggest that as corporal punishment becomes less socially accepted, its continued use may increasingly reflect deeper familial and structural vulnerabilities.